Workplace Stress and Physiological Indices Correlation Study Results - Dondonkhuu, Otgonbaatar; Tserenkhuu, Lkhagvasuren; Nyam, Naranbaatar; Jurmeddorj, Munkhkhand (Central Asian Journal of Medical Sciences, 2021)
Objective: Numerous studies demonstrated that while performing diverse routines in hospitals, nurses often face overcommitment and low social support. We have aimed in this study to address work-related stress level of nurses working at referral hospitals in Mongolia through determining the stress induced changes in blood pressure as well as alpha-amylase level in saliva. Methods: The study involved a totally of 473 nurses from tertiary referral hospitals of Mongolia. We employed the Work Stress Profile questionnaire of Rice and Likert scale in measuring the questions. Additionally, we measured the α-amylase level in the saliva of nurses. The arterial blood pressure, level of glucose in blood and heart pulse were evaluated by a cross-sectional model. Results: The study was conducted by collecting an age group similar to the age pyramid of nurses working in referral hospitals. The participants illustrated low levels of work stress in 7.6%, medium levels in 27.1%, and high levels of work stress in 65.3%, respectively. When we examine whether the level of stress exposure of nurses differs between the groups by high, medium, and low levels of workplace stress, the analysis of one factor variance confirms the statistical real difference (F = 3.071), (p = 0.028). The study results revealed that long lasting accumulated work stress triggers hypertension. Conclusion: The workplace stress of the nurses depends on many different physiological factors.